2009
DOI: 10.1002/kin.20442
|View full text |Cite
|
Sign up to set email alerts
|

effect of initial reagent concentrations on the oscillatory behavior of the BZ reaction in a batch reactor

Abstract: A detailed investigation on resorcinol as the Belousov-Zhabotinsky (BZ) oscillator in manganese(II) ion catalyzed reaction system with inorganic bromate (oxidant) and acetone (cosubstrate) was carried out in aqueous sulfuric acid medium (1.3 M). The aforesaid reagents were mixed with various concentrations to evolve the effective concentrations at which the reaction system exhibited better oscillations. The various oscillatory parameters such as time period (t p ), induction period (t in ), frequency (v), ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…This dependence of the oscillatory characteristics such as the induction period and time period is justified on the basis of the FKN mechanism 3,4, according to which the overall BZ reaction may be divided into the following three processes: consumption of bromide ion (process A), an autocatalytic reaction of bromous acid with the oxidation of catalyst (process B), and an organic reaction with the reduction of the catalyst (process C) From the data recorded in Table II, it is observed that with an increase in [BrO − 3 ], the induction period decreases. It is assumed that with an increase in the bromate concentration there is faster accumulation of the bromoderivative of aromatic substrate, thereby, shortening the induction period 19–21. The bromate chemistry harbors the autocatalytic step, which involves the single electron oxidation carried out by BrO 2 • .…”
Section: Resultsmentioning
confidence: 99%
“…This dependence of the oscillatory characteristics such as the induction period and time period is justified on the basis of the FKN mechanism 3,4, according to which the overall BZ reaction may be divided into the following three processes: consumption of bromide ion (process A), an autocatalytic reaction of bromous acid with the oxidation of catalyst (process B), and an organic reaction with the reduction of the catalyst (process C) From the data recorded in Table II, it is observed that with an increase in [BrO − 3 ], the induction period decreases. It is assumed that with an increase in the bromate concentration there is faster accumulation of the bromoderivative of aromatic substrate, thereby, shortening the induction period 19–21. The bromate chemistry harbors the autocatalytic step, which involves the single electron oxidation carried out by BrO 2 • .…”
Section: Resultsmentioning
confidence: 99%
“…The induction period is observed due to the accumulation of crucial concentration of the organic iodinated species prior to the commencement of oscillations. [16][17][18] The steps (3) and (4) in the above skeleton mechanism describe the iodination of organic substrate, where S and S(enol) denote organic substrate and its enolic form respectively and IS stands for the iodinated organic substrate. But, the tyrosine added to the system as additive has favorable iodination sites and undergoes iodination.…”
Section: Effect Of [Tyrosine] As An Additivementioning
confidence: 99%
“…Oscillatory chemical reactions [1,2], which are very sensitive, are disturbed by various small interfering factors, making them useful as an advanced analytic technique for trace substances. These systems generally include the Belousov-Zhabotinsky(BZ) [3][4][5], Bray-Liebhafsky(BL) [6], and Briggs-Rauscher(BR) [7] oscillation systems. In particular, BZ reactions have been extensively studied to elucidate their mechanisms and to model the wider range of excitable media.…”
Section: Introductionmentioning
confidence: 99%